The Secret Keeper : A Novel - Morton, Kate 1976- (New York : Atria Books, 2012)
Withdrawing from a family party to the solitude of her tree house, sixteen-year-old Laurel Nicolson witnesses a shocking murder that throughout a subsequent half century shapes her beliefs, her acting career, and the lives of three strangers from vastly different cultures.
Keywords: Secrecy -- Fiction; Actresses -- Fiction -- England; Great Britain -- Fiction -- Social life and customs; Mystery fiction